The Polyanalgesic Consensus Conference (PACC): Recommendations for Intrathecal Drug Delivery: Guidance for Improving Safety and Mitigating Risks. Issue 2 (2nd January 2017) - Deer, Timothy R.; Pope, Jason E.; Hayek, Salim M.; Lamer, Tim J.; Veizi, Ilir Elias; Erdek, Michael; Wallace, Mark S.; Grider, Jay S.; Levy, Robert M.; Prager, Joshua; Rosen, Steven M.; Saulino, Michael; et al.
Abstract : Introduction: Intrathecal therapy is an important part of the pain treatment algorithm for chronic disease states. The use of this option is a viable treatment strategy, but it is inherent for pain physicians to understand risk assessment and mitigation. In this manuscript, we explore evidence and mitigating strategies to improve safety with intrathecal therapy. Methods: A robust literature search was performed covering January 2011 to October 9, 2016, in PubMed, Embase, MEDLINE, Biomed Central, Google Scholar, Current Contents Connect, and International Pharmaceutical Abstracts. The information was cross‐referenced and compiled for evidence, analysis, and consensus review, with the intent to offer weighted recommendations and consensus statements on safety for targeted intrathecal therapy delivery. Results: The Polyanalgesic Consensus Conference has made several best practice recommendations to improve care and reduce morbidity and mortality associated with intrathecal therapy through all phases of management. The United States Prevention Service Task Force evidence level and consensus strength assessments are offered for each recommendation. Conclusion: Intrathecal therapy is a viable and relatively safe option for the treatment of cancer‐ and noncancer‐related pain. Continued research and expert opinion are required to improve our current pharmacokinetic and pharmacodynamic model of intrathecal drug delivery, as this will undoubtedly improve safety and efficacy.